PELESTARIAN TAPIS CORAK INUH MELALUI PEMBIAYAAN FINTECH DI KABUPATEN LAMPUNG SELATAN - Maulidiana, Lina; Dewi , Ade Sandra; Pujiati , Ani; Setia, Wahyu Darma; Pramudita, Rika (Jurnal Abdimas Bina Bangsa, 2024)
The community service activity titled "Preserving Tapis Corak Inuh Through Fintech Financing in South Lampung Regency" aligns with the current digital era advancements. This activity, which takes place from August to September 2024, includes topics on financial management in the fintech era, digital marketing training, creating fintech accounts, and online sales training. The material will be delivered at Hotel Batiqa, while visits and practical sessions will be conducted at Tapis Corak Inuh. The objective of this activity is to enhance the participants' understanding and skills in utilizing digital technology for business at Tapis Corak Inuh. Additionally, this community service activity introduces participants to the relationship between wise financial management in the fintech era, digital marketing training, creating fintech accounts, and online sales training. The results of this activity indicate an improvement in the participants' knowledge and interest in the topics covered during the community service, as well as benefits in terms of enhanced skills in managing finances and digital business.